The Effects of Probiotic Lactobacillus casei Shirota Strain in Patients with Allergic Rhinitis Symptoms - Asti Widuri; Lilis Suryani (Intelektual Pustaka Media Utama, 2015)
Allergic rhinitis is inflammatory reactions mediated by immunoglobulin E, after exposure to allergens. The symptoms are sneezing, runny nose and nasal congestion. Allergic rhinitis can be alleviated by the use of specific probiotics selected to confer immune effects, which can be demonstrated in the intestinal tract prior to an allergic reaction. The specific strains used in this study were selected based on their anti-inflammatory properties and an expected effect in promoting a Th1 type of immune response. To review the benefits of probiotics of Lactobacillus casei L Shirota strain in preventing allergy attacks that inhibit the production of IgE, IL-4 and reduce the symptoms. To review the benefits of probiotics of Lactobacillus casei L Shirota strain in preventing allergy attacks that inhibit the production of IgE, IL-4 and reduce the symptoms. The study design was quasi-experimental with pre and post test design. The subject were 45 patients who had a history of allergic rhinitis and positif skin prickt test result and filled out the questionnaires to get the allergic symptoms. The blood samples were taken for examining the IgE and IL-4 levels then after giving milk containing probiotics for 1 month, the researcher did the same examination. The mean IgE and IL-4 levels decrease before and after supplementation probiotics from 291.88 IU / L and 22.48 pg/ml to 141.43 IU / L and 17.83 pg/ml. The result of the statistical analysis paired t-test test was p = 0.00 on IgE level and p=0,056 on IL-4 level. The allergic rhinitis symptoms decreased significantly, the presentage of patients who had persistent and moderate 17.78% to 0% , who had persistent and mild 44.44% to 4.44%, who had intermittent and moderate 13.33% to 2.22%,and who had intermittent and mild 24.44% to 93.33%. Based on the Wilcoxon signed rank test showed a significance value of P = 0.00. Conclusion Probiotics is useful in preventing allergy attacks that inhibit the production of IgE, IL-4 and reduce the symptoms.